DOLZARB PROBLEMS OF EPIDEMIOLOGY AND PREVENTION OF DEGENERATIVE SPINE INJURIES (World Bulletin of Public Health, 2024)
The scientific value of the research results, suggested suggestions and conclusions are that the epidemiological information provided to all levels of health care (medical brigade, general practitioners, family and polyclinic doctors, traumatology and neurosurgery inpatients/centers, vertebrology centers, emergency and ambulance research centers) – the clinical approach helps to understand the nature of degenerative spine damage and/or adaptation to it. On the scale of the regions of Uzbekistan, this causes or leads to the development and implementation of early safe detection, treatment, prognosis of the disease, as well as the development and implementation of regional specific complex preventive-prophylactic programs
Keywords: Chronic non-infectious diseases; pathologies of degenerative damage to the spine; intervertebral disc herniation.